Study on sedimentary model of Shanxi Formation – Lower Shihezi Formation in Da 17 well area of Daniudi gas field, Ordos Basin - Yang Chenyu; Yu Hang; Xie Hui; Peng Shunfeng; Tian Jiangfei; Gao Zhiwu; Luo Tian (Open Geosciences)
The Daniudi gas field in the Ordos Basin is a significant area for developing tight sandstone gas reservoirs in China. This study focuses on the Permian Shanxi and Lower Shihezi formations in the Da 17 well area, analyzing sedimentary model through petrological characteristics, physical properties, pore characteristics, and lithofacies characteristics. Findings reveal that the Shanxi Formation belongs to the deltaic plain sedimentary environment, which is divided into distributary channel and inter-channel, and identifies the microfacies of the main distributary channel and the sub-distributary channel. The Lower Shihezi Formation exhibits braided channel sediments, dividing them into channel bar sediments and flood plain sediments, and identifying isolated channel microfacies and superimposed channel microfacies. Analysis shows that sedimentation has an impact on reservoir properties through particle size, lithological characteristics, and sedimentary microfacies. The main distributary channel and superimposed sandbars are favorable microfacies for the formation of gas reservoirs. The porosity of the main diversion channel ranges from 8 to 13%, and the permeability ranges from 0.3 to 0.6 × 10−3 m2. The porosity of the superimposed sandbar ranges from 8 to 15%, with a permeability of 0.3–2.2 × 10−3 m2. This study provides a theoretical foundation advancing tight sandstone gas development in the Daniudi gas field.